Exploring EFL Learners’ Emotional Engagement with Authentic English Captions in Digital Reading - Indi Azimah; Dzulfikri (ETERNAL (English Teaching Journal), 2026)
In the digital era, social media has become a prominent source of authentic English input for English as a Foreign Language (EFL) learners. While previous studies have emphasized benefits such as vocabulary enhancement, motivation, and digital literacy, little attention has been given to how learners emotionally engage with emotionally charged captions frequently encountered on platforms like Instagram, TikTok, and X. Despite their linguistic simplicity, these captions frequently elicit emotional responses and personal reflection, indicating a potential role in language learning that extends beyond traditional comprehension. The present study investigates EFL learners’ emotional and cognitive engagement with such captions and examines how these factors relate to language learning behaviours. Employing a qualitative methodology, semi-structured interviews were conducted with purposively selected participants who regularly interact with English-language content on social media. Thematic analysis identified five principal themes: emotional resonance, cognitive reflection, language learning behaviour, platform influence, and frequency of exposure. Participants described translating captions, reflecting on personal experiences, and observing vocabulary growth as outcomes of engaging with emotionally charged texts. Participant reported that emotional connection appeared to support their comprehension and vocabulary acquisition, particularly when content aligned with their personal experiences. This study highlights the significance of affective factors in digital reading contexts and offers preliminary evidence that social media texts can function as meaningful resources in English language learning.